Gamified Learning Platforms: Enhancing Student Engagement and Achievement in Hybrid Classrooms - Abdul Wahid (Gudang Jurnal Multidisiplin Ilmu, 2024)
This research explores the impact of gamification on student engagement and learning outcomes in hybrid classrooms at SMA Negeri 1 Pinrang. The study aims to identify the role of gamified platforms in enhancing student participation and to analyze the relationship between student engagement and academic achievement. The research employs a qualitative approach, utilizing purposive and random sampling to select students from hybrid classrooms. Data were collected through gamification-based platforms, student engagement surveys, and academic performance tests. The findings indicate that the use of gamification significantly increases student engagement, motivation, and academic achievement, particularly when integrated into a hybrid learning environment. This study also highlights challenges such as technology access and the need for teacher training to maximize the benefits of gamification. The results provide practical recommendations for educators to implement gamified elements in their teaching strategies and for platform developers to enhance features that support hybrid learning. Future research should investigate the broader impacts of gamification, particularly on diverse learning styles and across different academic subjects.